Impact of information and communication technology in Nigerian small-to medium-sized enterprises - Okundaye, Kessington (2019)
Purpose – The purpose of this (qualitative, multiple-case) study is to determine how small-to medium-sized enterprise (SME) leaders in Nigeria use information and communication technology (ICT) adoption as a business strategy to increase profitability and compete globally. Design/methodology/approach – The participants for this study consisted of executive-level SME leaders who had the authority to approve ICT implementation within their respective organizations. Individual interviews were undertaken with participants to gain an understanding of their experience of determining the merits of and implementing ICT. The technology acceptance model, which specifies the relationship between perceived usefulness, perceived ease of use, attitude toward computer use and intention to use technology, was applied as a framework to explain the Nigerian SME’s ICT adoption strategies. Findings – Four major themes emerged from the data analysis: ICT adoption factors, ICT roles and benefits, role of government and SME success factors. The findings of this study may help SME leaders and government leaders address many of the factors inhibiting the adoption of ICT in SMEs in Nigeria. Practical implications – This study may ensure that SMEs are successful and able to create jobs, which in turn may help to promote socioeconomic development through adoption of ICT. Originality/value – The findings from this study contribute to the knowledge base regarding factors that affect ICT adoption by SME leaders as a business strategy to increase profitability and compete globally, particularly within SMEs in Lagos, Nigeria. It further addressed the gap in existing literature regarding other factors such as the influence of culture on ICT adoption, cost of ICT implementation, available ICT skills, infrastructure and ICT knowledge gap as the primary impeding factors of ICT adoption in Nigerian SMEs.